Superiority of Epstein-Barr Virus DNA in the Plasma Over Whole Blood for Prognostication of Extranodal NK/T Cell Lymphoma - Ha, Joo Young; Cho, Hyungwoo; Sung, Heungsup; Jung, Ah Ra; Lee, Yoon Sei; Lee, Sang-Wook; Ryu, Jin-Sook; Chae, Eun Jin; Kim, Kyung Won; Huh, Jooryung; Park, Chan-Sik; Kim, Dong-Joon; et al. (Frontiers in Oncology, 2020)
Background: Extranodal natural killer T cell lymphoma (ENKTL) is a rare subtype of non-Hodgkin lymphoma with invariable infection of lymphoma cells with Epstein-Barr virus (EBV), and the presence of EBV-DNA in the blood is a well-known prognosticator. However, there is no consensus on which blood compartment is more optimal for predicting survival outcomes. Methods: We analyzed 60 patients who were newly diagnosed with ENKTL from a prospectively collected database. EBV-DNA was measured in the whole-blood (WB) and plasma at the time of diagnosis and after treatment completion. Results: EBV-DNA was detected in pre-treatment WB and plasma in 37 (61.7%) and 23 (38.3%) patients, respectively. The presence of pre-treatment plasma EBV-DNA was significantly associated with advanced stage while presence of WB EBV-DNA did not. Positivity of pre-treatment plasma-EBV, but not WB EBV-DNA, was independently associated with poor PFS (HR, 4.22; P=0.001) and OS (HR, 8.38; P<0.001) in the multivariate analysis. After treatment completion, positivity of plasma-EBV was independently associated with poor PFS (HR, 9.41; P=0.002) and OS (HR, 32.38; P=0.003), whereas no significant association was observed between WB-EBV status and survival outcomes. Conclusions: Our results suggest that EBV-DNA in the plasma has better prognostic values than WB in patients with ENKTL.